Identifikasi dan Evaluasi Risiko Manajemen Rantai Pasok Komoditas Jagung dengan Pendekatan Logika Fuzzy - Suharjito, Suharjito; Marimin, Marimin; Machfud, Machfud; Haryanto, Bambang; Sukardi, Sukardi (Jurnal Manajemen dan Organisasi, 2010)
To meet the needs of the national corn on the feed industry that requires a continuous supply of raw materials with a definite quantity throughout the year, in the national maize production conditions that is not continuous and fluctuating, it is necessary supply planning and storage methods to avoid the risk of maize corn supply crisis form of food shortages or rising feed prices. One method is to apply the concept of supply chain risk management. The high level of dependence and complexity of networks makes supply chain of agricultural products supply chain is becoming more vulnerable to interference. The risk of supply chain disturbance can occur internally (the relation between the organization with a network of suppliers) and external (between network suppliers with the environment). Therefore it is necessary to identify and evaluate supply chain risks in order to avoid continuing problems that can occur at any point in the supply chain network. The objective of this study is to describe the model of identification and evaluation for maize supply chain risk. This model can be used to identify the dominant risk factors and variables at each level of supply chain so that it will be obtained appropriate recommendations action to anticipate them. Risk identification will be conducted with fuzzy AHP approach and risk evaluation would be done by using fuzzy logic with data input form the opinion of several experts maize supply chain.